2010
DOI: 10.1007/s00432-010-0942-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of targeted therapy using circulating epithelial tumor cells (CETC): the example of SERM therapy monitoring as a unique tool to individualize therapy

Abstract: PurposeIn malignant tumors, predictive markers have been developed with respect to targeted therapies. One of the first targeted therapies was the hormone-blocking treatment of tumors of the male and female reproductive system. A typical therapy in breast cancer is the use of the selective estrogen receptor modulator, tamoxifen. However, only some of the patients, positive for the target molecules, respond to the selected therapy. It would, therefore, be highly desirable to have a tool to promptly assess the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…This is in accordance with Tanaka et al [43] who showed that in lung cancer patients, CTC counts significantly increased along with tumor progression, especially with development of distant metastasis. For breast cancer, Pachmann et al [44] showed that an increase of circulating epithelial tumor cells was a strong indicator for a relapse. In summary, the isolation and characterization of individual tumor cells from the blood of patients known to have metastatic cancer hold tremendous potential for new biological insight with very real clinical applications [45].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with Tanaka et al [43] who showed that in lung cancer patients, CTC counts significantly increased along with tumor progression, especially with development of distant metastasis. For breast cancer, Pachmann et al [44] showed that an increase of circulating epithelial tumor cells was a strong indicator for a relapse. In summary, the isolation and characterization of individual tumor cells from the blood of patients known to have metastatic cancer hold tremendous potential for new biological insight with very real clinical applications [45].…”
Section: Discussionmentioning
confidence: 99%
“…CTCs have been proven to be useful prognostic markers in several carcinomas in which they correlate to disease progression and predict relapse 14,15 . In MCC, the presence of CTCs has been previously reported in 4 patients, typically as a single case 16,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Values were displayed in scattergrams and histograms. Both approaches enable the user to locate cells contained within the desired population for visual examination and to take fluoromicrographs [24].…”
Section: Methodsmentioning
confidence: 99%